2011
DOI: 10.1371/journal.pone.0019255
|View full text |Cite
|
Sign up to set email alerts
|

Synapsis and Meiotic Recombination in Male Chinese Muntjac (Muntiacus reevesi)

Abstract: The muntjacs (Muntiacus, Cervidae) have been extensively studied in terms of chromosomal and karyotypic evolution. However, little is known about their meiotic chromosomes particularly the recombination patterns of homologous chromosomes. We used immunostained surface spreads to visualise synaptonemal complexes (SCs), recombination foci and kinetochores with antibodies against marker proteins. As in other mammals pachytene was the longest stage of meiotic prophase. 39.4% of XY bivalents lacked MLH1 foci compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…A similar covariance was observed in humans [Lynn et al, 2002] and rhesus monkeys [Hassold et al, 2009]. The distribution of recombination events along individual bivalents was influenced by interference, as reported previously for other mammalian species [Froenicke et al, 2002;Sun et al, 2004;Basheva et al, 2008;Borodin et al, 2008;Yang et al, 2011].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A similar covariance was observed in humans [Lynn et al, 2002] and rhesus monkeys [Hassold et al, 2009]. The distribution of recombination events along individual bivalents was influenced by interference, as reported previously for other mammalian species [Froenicke et al, 2002;Sun et al, 2004;Basheva et al, 2008;Borodin et al, 2008;Yang et al, 2011].…”
Section: Discussionsupporting
confidence: 83%
“…In species in which individual chromosomes cannot be determined by multicolor FISH, the MLH1 foci distribution on chromosomes can be assessed by ranking SCs according to their length, as it was published for mice [Anderson et al, 1999], dogs [Basheva et al, 2008] and Chinese muntjac [Yang et al, 2011]. We report mean numbers of recombination events in individual SCs classified according to their length in the 4 studied species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that cell-tocell differences in numbers of recombination sites (reflected by the standard deviation of the mean; electronic supplementary material, table S2) were especially low in species with karyotypes comprising a high number of acrocentric chromosomes (dog-all acrocentric chromosomes; lemur-85% acrocentric chromosomes). The same pattern is found in mouse and Chinese muntjac, both of which have strictly acrocentric karyotypes, where standard deviations were similarly low (+ 2.0-2.7) [15,39]. On the other hand, species with karyotypes comprising metacentric and submetacentric chromosomes show high cell-to-cell variability in the mean number of MLH1 foci (see electronic supplementary material, table S1), and this was particularly pronounced in the rat (+6.2) and tiger (+5.9).…”
Section: (B) Mechanistic Factors Affect Crossover Distribution Along supporting
confidence: 65%
“…The vast majority of papers which focus on mammalian meiosis and the process of recombination deal with humans or mice [Lynn et al, 2002;Jensen-Seaman et al, 2004], but in recent years many other mammalian species have been studied [Borodin et al, 2007Basheva et al, 2008;Dumont and Payseur, 2011;Garcia-Cruz et al, 2011;Yang et al, 2011;Segura et al, 2013;Vozdova et al, 2013;Al-Jaru et al, 2014;Mary et al, 2014].…”
mentioning
confidence: 99%